Adnexal torsion recurrence—is the adnexal twist degree a risk factor? A retrospective cohort study. (30th May 2021) - Bart, Y; Mohr‐Sasson, A; Yousefi, S; Goldenberg, M; Meyer, R; Toussia‐Cohen, S; Eyal, Y; Mazaki‐Tovi, S; Mashiach, R
Abstract : Objective: To evaluate whether the adnexal twist degree is related to torsion recurrence and whether there is a dose‐dependent correlation. Design: A retrospective cohort study. Setting: Single tertiary medical centre. Population: The study includes non‐pregnant patients operated, for the first time, for adnexal torsion, between 2011 and 2018. Methods: Information regarding the degree of adnexal twist was collected from surgical reports. Recurrence was identified using a computerised database and ascertained via telephone with a response rate of 87.2% (253/290). Main outcome measures: Adnexal torsion recurrence rate. Results: A total of 182 women who had undergone laparoscopic detorsion met the inclusion criteria. Twenty‐two had torsion recurrence (12.1%). Adnexal twist degree in the primary event was associated with a higher recurrence risk: 4.3% of women with twist degree ≤360 ( n  = 3/70), 14.5% of women with twist degree of 361–720 ( n  = 9/62) and 20% of women with twist degree >720 ( n  = 10/50) ( P  = 0.03). The median twist degree was 540 (interquartile range [IQR] 360–855) and 720 (IQR 675–1080) degrees in the control and study groups, respectively ( P  = 0.005). Additional possibly associated factors for recurrence were evaluated. Age emerged as a possible risk factor, with a median age of 19 years in the recurrence group (IQR 14–27 years) versus 28.5 (IQR 19–36 years) in the non‐recurrence group ( P  < 0.01). Logistic regression analysis revealed that together with age, adnexal twist degree remained significantly associated with torsion recurrence (odds ratio [OR] 1.98, 95% CI 1.09–3.61; P  = 0.02). Conclusion: Adnexal twist degree was found to be positively associated with the risk of torsion recurrence. Tweetable abstract: Adnexal twist degree was found to be positively associated with the risk of torsion recurrence. Tweetable abstract: Adnexal twist degree was found to be positively associated with the risk of torsion recurrence.